Studi Adopsi Standar Kompetensi Internasional Air Traffic Controller On The Job Training Instructors Kedalam Kurikulum Pelatihan Air Traffic Controller On The Job Training Instructors - Sonhaji, Imam; Jatmoko, Djoko; Wijaksono, Agung Wahyu (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
The professionalism of the Air Traffic Controller is a standard for air traffic service so that a good process is needed at all stages, one of the stage is in the On-the-Job Training process, On-the-Job Training Instructor shall comply with required competencies through the gap analysis method by comparing international competences based on Document 9868 Procedures for Air Navigation Services Training with competencies on ATC On the Job Training Instructor training curriculum. The result is that there are 3 (three) international competencies that need to be inserted into the ATC On the Job Training Instructor training curriculum, namely mentoring skills competencies, Collaboration Skills, and Ethics and Integrity skills.